Narrative Analysis From The Perspective Of Personality Psychology On The Character Of Mrs. Martopo Manuscript Orang Kasar By Anton Chekov - Precillia, Monita; Arimbi, Dewi; Darmadi, Dedi (Creativity And Research Theatre Journal, 2024)
The research titled "Narrative Analysis Using Jungian Personality Psychology Perspective with Focus on the Character Mrs. Martopo in the Rough People Manuscript by Anton Chekhov aims to analyze gender issues in female characters in the manuscript using Carl Gustav Jung's perspective on personality psychology. This study applies narrative analysis using qualitative method with data collection techniques from the manuscript, translations, and relevant sources. Gender issues on Mrs. Martopo include her husband's infidelity, gender roles, and social adaptation. This narrative analysis provides new insights into the relationship between literature, personality psychology, and Jungian Theory, depicting how psychological understanding can provide interpretive depth to characters in literary works. This research can serve as a foundation for further research in the fields of theater, literature, psychology, and gender studies.